Bioaerosols in the Barcelona subway system. (26th October 2016) - Triadó‐Margarit, X.; Veillette, M.; Duchaine, C.; Talbot, M.; Amato, F.; Minguillón, M. C.; Martins, V.; de Miguel, E.; Casamayor, E. O.; Moreno, T.
Abstract: Subway systems worldwide transport more than 100 million people daily; therefore, air quality on station platforms and inside trains is an important urban air pollution issue. We examined the microbiological composition and abundance in space and time of bioaerosols collected in the Barcelona subway system during a cold period. Quantitative PCR was used to quantify total bacteria, Aspergillus fumigatus, influenza A and B, and rhinoviruses. Multitag 454 pyrosequencing of the 16S rRNA gene was used to assess bacterial community composition and biodiversity. The results showed low bioaerosol concentrations regarding the targeted microorganisms, although the bacterial bioburden was rather high (10 4 bacteria/m 3 ). Airborne bacterial communities presented a high degree of overlap among the different subway environments sampled (inside trains, platforms, and lobbies) and were dominated by a few widespread taxa, with Methylobacterium being the most abundant genus. Human‐related microbiota in sequence dataset and ascribed to potentially pathogenic bacteria were found in low proportion (maximum values below 2% of sequence readings) and evenly detected. Hence, no important biological exposure marker was detected in any of the sampled environments. Overall, we found that commuters are not the main source of bioaerosols in the Barcelona subway system.